Basic Techniques and Approaches in Preserving the Endangered Betawi Language - Iskandarsyah Siregar (Budapest International Research and Critics University, 2023)
One of the most important aspects of civilisation that must be preserved is language. Similarly, the processes of civilisation are exerting growing strain on the Betawi language. Determining the optimum method for preserving, maintaining, and rehabilitating the Betawi language is critical. This page is the result of a decades-long investigation of the Betawi language. The interdisciplinary method considerably aids researchers in locating, analysing, and concluding evidence. Because of the numerous circumstances in the subject, researchers attempt to employ all ways to identify the optimal way. Finally, multidimensional, holistic, and comprehensive methodologies and approaches are used to choose the best course of action to save the Betawi language from extinction. Measurable steps taking into account various aspects are the key to obtaining the expected research results, so they can be directly applied to achieve tangible benefits to the community.